China's A2/AD strategy and the role of technology : on the path towards a RMA? - Dingeldey, Philipp Martin (2015)
The following paper engages with the questions what role technology plays in China's A2/AD strategy and military modernisation, and whether this means that China is on the path towards a revolution in military affairs (RMA). In order to answer the stated questions the author first outlines a general understanding and different views on what a RMA is. Once a general understanding of the concept is established, the paper continues with exploring the relationship between Technology and innovation, two issues the RMA is generally associate with, and takes a look at China's defence industry. This is followed by a discussion about China's so called anti-access/area denial (A2/AD) strategy, and whether it can just be seen as a modem version of sea denial. Last but not least, the paper analyses China's military in regard to the initially posed question, focusing on achievements since the 1990s, technological developments, and shortcomings. Finally, a conclusion will be draw stating that China is not on the path towards a RMA, due to inherent shortcomings in its technology integration, defence economy, and level of "jointness."